Pemberian Kombinasi Pupuk Kandang Kambing dan Pupuk N, P, K terhadap Serapan Hara N, P, K serta Hasil Tanaman Jagung (Zea mays L.) di Tanah Ultisol - Rizki, Saffira Nurfadilah; Hayati, Rita; Widiarso, Bambang (Soil Science Department, Faculty of Agriculture, Tanjungpura University, 2025)
Ultisol soil is one of the soil types that are widespread in Indonesia, especially West Kalimantan, and has the potential to be used as corn (Zea mays L.) cultivation land. Based on its characteristics, Ultisol is less supportive of plant growth because it has an acidic pH (